Investigation on Student Accessing Information for ICT- Learning Approaches - Haziana, Abdul Halim; Ananthi, Krishnasami; Yanti Hidayu, Aziz; Noor Suhani, Sulaiman; Adzhar, Kamaludin (GBMR, 2018)
Purpose: The purpose of this study is to investigate the level of student’s performance using the traditional approach and the integration of e-learning in teaching and learning process. Also to investigate the frequency of student’s accessing the multimedia contents, forums, and quizzes using multimedia learning